2010
DOI: 10.1107/s0108768110024080
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigation of GeSb6Te10 and GeBi6Te10 intermetallic compounds in the chalcogenide homologous series

Abstract: The crystal structures of GeSb(6)Te(10) and GeBi(6)Te(10) were scrutinized using an X-ray powder diffraction method, which revealed that these compounds crystallize in trigonally distorted cubic close-packed structures with a 51-layer period (R3m). Each layer consists of a triangular atomic net; Te atoms occupy their own specific layers, whereas Ge, Sb and Bi atoms are located in the other layers. In these pseudobinary compounds, random atomic occupations of Ge and Sb/Bi are observed and the layers form two ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…In fact, as early as 1998, Karpinsky et al and Shelimova et al have proposed that the stable (GeTe) n –(Sb 2 Te 3 ) m compounds exhibit Ge/Sb intermixing in cation planes. Also, several articles confirmed such model of Ge/Sb intermixing in the GST blocks . As mentioned above, recent experiments demonstrated again that the intermixing is a general phenomenon in GST‐SLs fabricated by MBE, PLD, and sputtering.…”
Section: The Atomic Structure Of Gst‐slmentioning
confidence: 54%
“…In fact, as early as 1998, Karpinsky et al and Shelimova et al have proposed that the stable (GeTe) n –(Sb 2 Te 3 ) m compounds exhibit Ge/Sb intermixing in cation planes. Also, several articles confirmed such model of Ge/Sb intermixing in the GST blocks . As mentioned above, recent experiments demonstrated again that the intermixing is a general phenomenon in GST‐SLs fabricated by MBE, PLD, and sputtering.…”
Section: The Atomic Structure Of Gst‐slmentioning
confidence: 54%
“…12 A homologous series of pseudobinary compounds, nGeTemBi 2 Te 3 , was intensively studied in terms of its thermoelectric, galvanomagnetic, and thermomagnetic properties. [27][28][29][30] Among them, GeBi 2 Te 4 was theoretically proposed as a member of the 3D TIs. [31][32][33] It was experimentally verified to be a 3D TI possessing a single TSS by an angleresolved photoemission spectroscopy (ARPES) experiment.…”
Section: Introductionmentioning
confidence: 99%
“…6), it becomes increasingly difficult to obtain a cubic phase experimentally. It has been found that Sb 2 Te 3 -rich compounds exhibit stable hexagonal structures with very elongated primitive cells: for instance, GeSb 6 Te 10 displays a 51-layer periodicity along the c direction4041. No rocksalt-like structure has been reported in these experimental works.…”
Section: Discussionmentioning
confidence: 85%